2022
DOI: 10.22219/jrak.v12i3.22782
|View full text |Cite
|
Sign up to set email alerts
|

Internal Auditor Competency Gap: Perception Of Students, Academics And Practitioners

Abstract: The purpose of this study is to investigate internal auditor competency gap by comparing the perceptions between students, academics, and practitioner. Questionnaires were sent to 1009 respondents who meet the criteria using google form. The questionnaire was divided into two parts. The first part, we ask respondents’ perception related with hard skill needed by internal auditor, the second part discussed soft skill required to prepare agile and adaptive internal auditor. This study found two main gaps between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The advisory group noted that as data governance matures, internal auditors will likely be increasingly looked to for leadership in this area. These findings are consistent with Setyaningrum et al (2022), who find a disconnect between Indonesian professionals and academics related to technology and emerging (soft) skills.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…The advisory group noted that as data governance matures, internal auditors will likely be increasingly looked to for leadership in this area. These findings are consistent with Setyaningrum et al (2022), who find a disconnect between Indonesian professionals and academics related to technology and emerging (soft) skills.…”
Section: Introductionsupporting
confidence: 92%
“…Hence, this article serves as a crucial resource for organisations planning future training programmes and hiring strategies, helping to bridge potential perception gaps (e.g. Setyaningrum et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The result is possible that independence is no longer the crucial thing that is owned by an auditor. Previous research found the importance of soft skills regarding knowledge of performance standards which is seen as more important haven by an auditor (Setyaningrum et al, 2022). In agency theory, there is a difference in interests between the principal and the agent (Jensen & Meckling, 1976).…”
Section: Discussionmentioning
confidence: 98%
“…This particular training regime aims to improve and develop the skills that may be lacking in undergraduate programmes (Maelah et al 2012). Focusing on the internal auditor competency gap, practitioners placed a higher emphasis on soft skills than on hard skills (Setyaningrum, Mita & Rosdini 2022). Professional skills are also referred to as soft skills, key skills, vocational skills and employability skills (Coetzee & Du Plessis 2020;Crawford, Helliar & Monk 2011;De Lange, Jackling & Gut 2006;Kwarteng & Mensah 2022;Ng, Schweitzer & Lyons 2010;Succi & Canovi 2020;.…”
Section: Discussionmentioning
confidence: 99%